Incorporating gene expression and environment for genomic prediction in wheat - Liu, Jia; Gock, Andrew; Ramm, Kerrie; Stops, Sandra; Phongkham, Tanya; Norman, Adam; Eastwood, Russell; Stone, Eric; Dillon, Shannon (Frontiers in Plant Science, 2025)
IntroductionThe adoption of novel molecular strategies such as genomic selection (GS) in crop breeding have been key to maintaining rates of genetic gain through increased efficiency and shortening the cycle of evaluation relative to conventional selection. In the search for improved methodologies that incorporate novel sources of variation for the assessment of genetic merit, GS remains a focus of crop breeding research globally. Here we explored the role transcriptome data could play in enhancing GS in wheat.MethodsAcross 286 wheat lines, we integrated phenotype and multi-omic data from controlled environment and field experiments including ca. 40K single nucleotide polymorphisms (SNP), abundance data for ca. 50K transcripts as well as meta-data (e.g. categorical environments) to predict individual genetic merit for two agronomic traits, flowering time and height. We evaluated the performance of different model scenarios based on linear (GBLUP) and Gaussian/nonlinear (RKHS) regression in the Bayesian analytical framework. These models explored the relative contributions of different combinations of additive genomic (G), transcriptomic (T) and environment (E), with and without considering non-additive epistasis, dominance and genotype by environment (G × E) random effects.ResultsIn controlled environments, where traits were measured under contrasting daylength regimes (long and short days), transcriptome abundance outperformed other random effects when considered independently, while the model combining SNP, environment and G × E marginally outperformed the transcriptome. The best performing model for prediction of both flowering and height combined all data types, where the GBLUP framework showed slightly better performance overall compared with RKHS across all tests. Under field conditions, we found that models combining all variables were superior using the RKHS framework. However, the relative contribution of the transcriptome was reduced.DiscussionOur results show there is a predictive advantage to direct inclusion of the transcriptome for genomic evaluation in wheat breeding for traits where G × E is a factor. However, the complexity and cost of generating transcriptome data are likely to limit its feasibility for commercial breeding at this stage. We demonstrate that combining less costly environmental covariates with conventional genomic data provides a practical alternative with similar gains to the transcriptome when environments are well characterised.